2012
DOI: 10.1002/jor.22291
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional polymorphism in the promoter region of TLR‐3 with osteoarthritis: A two‐stage case–control study

Abstract: Recent studies have suggested that polymorphisms in toll-like receptor 9 (TLR-9), an endosomal TLR, are associated with knee osteoarthritis (OA). TLR-3, -7, and -8 are also found on the surface of endosomes and to investigate whether similar associations exist with polymorphisms in these TLR genes we performed a two-stage case-control study and genotyped 11 TLR single nucleotide polymorphisms (SNPs) in 823 OA cases and 594 healthy controls by polymerase chain reaction restriction fragment length polymorphism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
1
32
1
3
Order By: Relevance
“…However, contrasting results were also observed. Hsin-Yi et al observed that the rs3775291 has no significant genotype and allele association between osteoarthritis cases and healthy controls in a Chinese Han population [31]. In this study, we did not find an association in the genotype and allele frequencies of rs3775291 between PE patients and healthy pregnant women.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…However, contrasting results were also observed. Hsin-Yi et al observed that the rs3775291 has no significant genotype and allele association between osteoarthritis cases and healthy controls in a Chinese Han population [31]. In this study, we did not find an association in the genotype and allele frequencies of rs3775291 between PE patients and healthy pregnant women.…”
Section: Discussioncontrasting
confidence: 44%
“…In this study, we did not find an association in the genotype and allele frequencies of rs3775291 between PE patients and healthy pregnant women. Hsin-Yi et al have shown that rs3775296, located in the 5′-UTR of TLR3, is associated with elevated TLR3 expression and susceptibility to knee osteoarthritis in a Chinese Han population [31]. Moreover, the rs3775296-T allele was associated with photosensitivity and anemia of system lupus erythematosus in females in a Taiwanese population [32].…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been suggested that promoter polymorphisms in TLR-3 (c.1377C/T, _7 C/A) influence gene expression in response to inflammatory cytokines and causes transcriptional modulation in TLR-3. 22 Human TLR-3 promoter region contains a functional IFN-stimulated response element/IRF element. 23 TLR-9 1237T/C SNP confers regulatory effects on TLR-9 transcription; higher transcriptional activity was seen in the presence of the CC allelic variant with moderate increase in promoter activity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have revealed that some SNPs in TLR3 are associated with several human diseases, such as OA [10], nasopharyngeal carcinoma [26] and systemic lupus erythematosus (SLE) [27]. Here, the -7C/A polymorphism of TLR3 was strongly associated with ESRD.…”
Section: Discussionmentioning
confidence: 85%
“…Single-nucleotide polymorphisms (SNPs) in TLR3 have been correlated with diseases such as osteoarthritis (OA) [10], type 1 diabetes mellitus (T1DM) [11], asthma [12] and bladder cancer [13]. Previous studies have indicated that the presence of TLR3 SNPs influences promoter activity (gene expression), mRNA conformation (stability) and subcellular localisation of mRNAs and/or protein structure and function.…”
Section: Introductionmentioning
confidence: 99%